Prognostic factors and treatment outcomes of spinal osteosarcoma: Surveillance, epidemiology, and end results database analysis - Wang, Jing; Ni, Xiang-zhi; Yang, Ming-lei; Huang, Xing; Hou, Shu-ming; Peng, Cheng; Cao, Jia-shi; Liu, Tie-Long (Frontiers in Oncology, 2023)
Objective Spinal osteosarcoma is a rare osseous neoplasm. The aim of this article is to comprehensively analyze the demographic features, clinicopathologic characteristics and prognoses of spinal osteosarcoma patients using Surveillance, Epidemiology, and End Results (SEER) database. Materials and methods SEER data were reviewed to identify patients diagnosed with spinal osteosarcoma between 1975 and 2016. Overall survival (OS) and disease-speciﬁc survival (DSS) were determined. Cox-regression proportional hazards models and Kaplan-Meier methods were used for both univariate and multivariate analyses. Results In total, 668 patients with spinal osteosarcoma were identified. Mean age at diagnosis was 45.2 years with 67.5% of patients were younger than 60s, and 53.1% of patients were males. The overall median survival time of patients was 15 months, and the 5-year OS was 16.8%. On multivariate analysis of spinal osteosarcoma patients, age≥60 (HR=2.271, p = 0.008), high grade (HR=1.323, p = 0.008), regional stage (HR=1.658, p = 0.017), metastasis stage (HR=3.045, p < 0.001) and no-surgery treatment (HR=1.761, p < 0.001) were negatively associated with OS. In terms of DSS, gender (HR=0.657, p = 0.044), tumor grade (HR=1.616, p = 0.006), tumor stage (HR=3.329, p = 0.011; HR=7.983, p < 0.001) and radiotherapy (HR=0.606, p = 0.031) were independent prognostic factors. Conclusion Based on SEER data analysis, male, high tumor grade, regional stage, metastasis stage and radiotherapy are independent predictors of poor survival in spinal osteosarcoma. The treatment of spinal osteosarcoma still faces serious challenges. In future, the researches of the clinical impact and survival outcomes of the emerging targeted and immune therapies are warranted to overcome this survival stalemate.